Antimicrobial activities of fungi derived from the gorgonian sea fan Annella sp. & their metabolites - Sita Preedanon (2018)
© 2016, National Institute of Science Communication and Information Resources (NISCAIR). All rights reserved. One hundred and sixty-three fungi isolated from gorgonian sea fan Annella sp. were screened for antimicrobial activity against human pathogens. Forty-seven percents of the isolates produced antimicrobial metabolites against at least one pathogen with minimum inhibitory concentrations (MIC) ranged from 1 to 1,280 µg mL-1. Crude extracts from 16%, 21%, 18% and 23% of the isolates inhibited standard strain of Staphylococcus aureus, methicillin-resistant S. aureus, Escherichia coli and Pseudomonas aeruginosa, respectively. Eighteen percents of the isolates displayed antifungal activity against Microsporum gypseum while only 3% inhibited Cryptoccocus neoformans and Candida albicans. Potential isolates were identified by morphological and molecular characteristics. Twenty-nine pure compounds isolated from ten isolates were evaluated for antimicrobial activity. Griseofulvin from Nigrospora sp. PSU-F13 exhibited the best activity against M. gypseum (MIC 2 µg mL-1). The result indicates that sea fan-derived fungi are a potential source of antimicrobial agents.